2021
DOI: 10.1021/acs.chemmater.0c04153
|View full text |Cite
|
Sign up to set email alerts
|

Complex Relationship between Side-Chain Polarity, Conductivity, and Thermal Stability in Molecularly Doped Conjugated Polymers

Abstract: Molecularly doped conjugated polymers with polar side chains are an emerging class of conducting materials exhibiting enhanced and thermally stable conductivity. Here, we study the electronic conductivity (σ) and the corresponding thermal stability of two polythiophene derivatives comprising oligoethylene glycol side chains: one having oxygen attached to the thiophene ring (poly­(3-(methoxyethoxyethoxy)­thiophene) (P3MEET)) and the other having a methylene spacer between the oxygen and the thiophene ring (poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(55 citation statements)
references
References 57 publications
(107 reference statements)
4
46
0
Order By: Relevance
“…In the first part of the paper, we study the charge transport and thermoelectric properties of P3MEET thin films vapor doped with FnTCNQ. P3MEET exhibits a maximum σ as high as 27.0 ± 3.7 S/cm upon doping with F4TCNQ, which matches our previous study 23 . Despite having higher EA levels, F2TCNQ/F1TCNQ‐doped P3MEET have a comparable maximum σ at 26.4 ± 3.1 S/cm and 20.1 ± 0.77 S/cm, respectively.…”
Section: Introductionsupporting
confidence: 89%
See 3 more Smart Citations
“…In the first part of the paper, we study the charge transport and thermoelectric properties of P3MEET thin films vapor doped with FnTCNQ. P3MEET exhibits a maximum σ as high as 27.0 ± 3.7 S/cm upon doping with F4TCNQ, which matches our previous study 23 . Despite having higher EA levels, F2TCNQ/F1TCNQ‐doped P3MEET have a comparable maximum σ at 26.4 ± 3.1 S/cm and 20.1 ± 0.77 S/cm, respectively.…”
Section: Introductionsupporting
confidence: 89%
“…The IE of P3MEET is found to be 4.92 eV, whereas the EA values of F4TCNQ, F2TCNQ and F1TCNQ are determined to be 5.25, 5.10, and 5.01 eV, respectively (see details of CV measurements in ref. 23). As expected, the EA level decreases with decreasing fluorination level for three dopants.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A study by Dong et al revealed that introduction of a methylene spacer between the first side chain oxygen and polymer backbone reduces thermal dopant stability observed through the loss in conductivity at 130 °C when comparing to the same polymer with the EG motif directly bonded to the backbone. (Dong et al, 2020) This has also been observed for another series of EGfunctionalised derivatives of P3HT where the thermal stability at 80 °C decreased with increasing polar co-monomer content. (Finn et al, 2020) EG motifs have also been added to NDI derivatives to improve electrical conductivity of n-type polymers.…”
Section: Ongoing Materials Development and Future Directionssupporting
confidence: 55%